Protein microarrays with carbon nanotubes as multicolor Raman labels - Chen, Zhuo; Tabakman, Scott M; Goodwin, Andrew P; Kattah, Michael G; Daranciang, Dan; Wang, Xinran; Zhang, Guangyu; Li, Xiaolin; Liu, Zhuang; Utz, Paul J; Jiang, Kaili; Fan, Shoushan; et al. (Nature biotechnology, 2008)
The picomolar sensitivity of fluorescence-based protein detection limits the use of protein arrays in research and clinical diagnosis. Chen et al . use antibody-tagged single-walled carbon nanotubes as multicolor Raman labels to detect femtomolar levels of serum analytes over a wide dynamic range. The current sensitivity of standard fluorescence-based protein detection limits the use of protein arrays in research and clinical diagnosis. Here, we use functionalized, macromolecular single-walled carbon nanotubes (SWNTs) as multicolor Raman labels for highly sensitive, multiplexed protein detection in an arrayed format. Unlike fluorescence methods, Raman detection benefits from the sharp scattering peaks of SWNTs with minimal background interference, affording a high signal-to-noise ratio needed for ultra-sensitive detection. When combined with surface-enhanced Raman scattering substrates, the strong Raman intensity of SWNT tags affords protein detection sensitivity in sandwich assays down to 1 fM—a three-order-of-magnitude improvement over most reports of fluorescence-based detection. We use SWNT Raman tags to detect human autoantibodies against proteinase 3, a biomarker for the autoimmune disease Wegener's granulomatosis, diluted up to 10 7 -fold in 1% human serum. SWNT Raman tags are not subject to photobleaching or quenching. By conjugating different antibodies to pure 12 C and 13 C SWNT isotopes, we demonstrate multiplexed two-color SWNT Raman-based protein detection.